Microwave-assisted alkaline extraction of galactan-rich rhamnogalacturonan I from potato cell wall by-product. (1st January 2016) - Khodaei, Nastaran; Karboune, Salwa; Orsat, Valérie
Highlights: Microwave assisted-alkaline extraction of potato rhamnogalacturonan I (RG I) was optimized. Microwave power and solid/liquid ratio exhibited an adverse interactive effect on yield. An adverse interaction between KOH concentration and time affected galactose content. A compromise between extraction parameters is a key for minimizing RG I debranching. RG I functional properties were comparable or superior to galactan and homogalacturonan. Abstract: Galactan-rich rhamnogalacturonan I (RG I), exhibiting promising health benefits, is the most abundant polysaccharide in potato pulp by-product. In the present study, the microwave-assisted alkaline extraction of galactan-rich RG I was investigated. Solid/liquid ratio was identified as the most significant parameter affecting linearly yield and galactose/rhamnose contents. Microwave power and solid/liquid ratio exhibited a significant adverse interactive effect on the yield. Galactose content of extracted polysaccharides can be modulated by compromising between KOH concentration and extraction time, which exhibited adverse interaction. Optimum conditions were identified using the established predicted models and consisted of treatment of potato cell wall at solid/liquid ratio of 2.9% (w/v) with 1.5 M KOH under microwave power of 36.0 W for 2.0 min. Yield of intact galactan-rich RG I of 21.6% and productivity of 192.0 g/L h were achieved. The functional properties of RG I-rich polysaccharides were comparable or superior to potato galactan and oranges homogalacturonan.